Alternative landfill soil/vegetation covers at Rocky Mountain Arsenal: could difference in plant roots between covers contribute to differences in cover function? - Brown, Cynthia S., author; Jamiyansharav, Khishigbayar, author (Colorado State University. Libraries, 2016)
In May 2015, the Army notified Regulatory Agencies that the amount of water collected by Lys 001 and Lys 002 on the Shell Disposal Trench RCRA-equivalent cover exceeded the compliance standard of 1.3 mm/yr (Navarro report, 17 Sep 2015). The purpose of the project reported here is to Investigate root development as possible contribution to this excessive percolation.
Could difference in plant roots between covers contribute to differences in cover function?
Keywords: shell disposal trench; integrated cover systems; natural grassland area; soil washing; root scanning; root drying & weighing